Finite Element Analysis of Mobile-bearing Unicompartmental Knee Arthroplasty： The Influence of Tibial Component Coronal Alignment - Zhu, Guang-Duo; Guo, Wan-Shou; Zhang, Qi-Dong; Liu, Zhao-Hui; Cheng, Li-Ming (Chinese medical journal, 2015)
Background： Controversies about the rational positioning of the tibial component in unicompartmental knee arthroplasty （UKA） still exist. Previous finite element （FE） studies were rare, and the results varied. This FE study aimed to analyze the influence of the tibial component coronal alignment on knee biomechanics in mobile-bearing UKA and find a ration range of inclination angles. Methods： A three-dimensional FE model of the intact knee was constructed from image data of one normal subject. A 1000 N compressive load was applied to the intact knee model for validating. Then a set of eleven UKA FE models was developed with the coronal inclination angles of the tibial tray ranging from 10° valgus to 10° varus. Tibial bone stresses and strains, contact pressures and load distribution in all UKA models were calculated and analyzed under the unified loading and boundary conditions. Results： Load distribution, contact pressures, and contact areas in intact knee model were validated. In UKA models, von Mises stress and compressive strain at proximal medial cortical bone increased significantly as the tibial tray was in valgus inclination 〉4°, which may increase the risk of residual pain. Compressive strains at tibial keel slot were above the high threshold with varus inclination 〉4°, which may result in greater risk of component migration. Tibial bone resection comer acted as a strain-raiser regardless of the inclination angles. Compressive strains at the resected surface slightly changed with the varying inclinations and were not supposed to induce bone resorption and component loosening. Contact pressures and load percentage in lateral compartment increased with the more varus inclination, which may lead to osteoarthritis progression. Conclusions： Static knee biomechanics after UKA can be greatly affected by tibial component coronal alignment. A rauge from 4° valgus to 4° varus inclination oftibial component can be recommended in mobile-bearing UKA.